Sites of violence : gender and conflict zones - Giles, Wenona Mary, 1949-; Hyndman, Jennifer (Berkeley : University of California Press, 2004)
Augmenting feminist analysis on conflict zones, this volume explores the gendered politics of ethno-nationalism 'honour-killings' in Iraq & Kurdistan, the civil war in Sudan & geographies of violence in Ghana, to investigate what happens when violence is invoked against people.
Gender and conflict in a global context / Wenona Giles and Jennifer Hyndman -- The continuum of violence: a gender perspective on war and peace / Cynthia Cockburn -- The sounds of silence: feminist research across time in Guatemala / Cathy Blacklock and Alison Crosby -- Like oil and water, with a match: militarized commerce, armed conflict, and human security in Sudan / Audrey Macklin -- No "safe haven": violence against women in Iraqi Kurdistan / Shahrzad Mojab -- From pillars of Yugoslavism to targets of violence: Interethnic marriages in the former Yugoslavia and thereafter / Mirjana Morokvasic-Müller -- Geographies of violence: women and conflict in Ghana / Valerie Pretson and Madeleine Wong -- Gender, the nationalist imagination, war, and peace / Nira Yuval-Davis -- Refugee camps as conflict zones: the politics of gender / Jennifer Hyndman -- The "purity" of displacement and the reterritorialization of longing: Muslim IDPs in the northwestern Sri Lanka / Malathi de Alvis -- Escaping conflict: Afghan women in transit / Asha Hans -- War, flight, and exile: gendered violence among refugee women from post-Yugoslav states / Maja Korac -- The gendered impact of multilateralism in the post-Yugoslav states: intervention, reconstruction, and globalization / Edith Klein -- New directions for feminist research and politics / Wenona Giles and Jennifer Hyndman.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Violence; Political violence; Social conflict; Women -- Crimes against; Sex role; Sex differences; Feminist theory; Violence; Violence politique; Conflits sociaux; Femmes -- Crimes contre; Rôle selon le sexe; Différences entre sexes; Théorie féministe.; violence; terrorism; sex role; social conflict; SOCIAL SCIENCE -- Violence in Society; SOCIAL SCIENCE -- Gender Studies; Feminist theory; Political violence; Sex differences; Sex role; Social conflict; Violence; Women -- Crimes against; Feminismus; Frau; Gewalt; Politik; Politischer Konflikt; Geweld; Etnische conflicten; Vrouwen; Sekserol; Aufsatzsammlung